The case of the stolen baseball cards - Preller, James; Speirs, John (New York : Scholastic, 1999)
When Eddie's baseball cards suddenly disappear, Jigsaw and Mila take on the case and begin their search to find both Eddie's missing property and those responsible for taking them.
"A Little apple paperback."
2-3
Keywords: Baseball cards -- Fiction; Mystery and detective stories